Long-term preclinical evaluation of a bare-metal stent (INA-Stent) in the iliac arteries of Macaca nemestrina - Wijayanti, Agustina Dwi; Arifianto, Dinar; Wijayanto, Hery; Purnomo, Agus; Budi, Setyo; Taufiq, Nahar; Yulianto, Heribertus Dedy Kusuma; Siswomihardjo, Widowati (Jurnal Medik Veteriner, 2026)
This study represents the final phase of a preclinical investigation assessing the outcomes of bare-metal stent (INA-Stent) implantation in the iliac arteries of Macaca nemestrina. The aim of the study was to evaluate the condition of the stent and to determine the presence or absence of restenosis and inflammation in the surrounding tissue. The INA-Stent was implanted in four healthy adult M. nemestrina. The animals were euthanized at 6- and 9-month intervals to enable clinical and histological evaluation of the implanted stents. This study specifically reports the terminal preclinical evaluation of the final M. nemestrina, in which the stent had been implanted for 36 months. The assessment was conducted to identify clinical signs and to determine the condition of the stent following surgical implantation in the iliac artery. The procedures included clinical evaluation, anesthesia, catheterization, intravascular optical coherence tomography (OCT), followed by euthanasia, necropsy, and scanning electron microscopy (SEM). Based on the SEM and OCT findings, the INA-Stent was well integrated into the arterial wall, did not induce chronic inflammation, and showed no evidence of restenosis at 36 months post-implantation.